2011
DOI: 10.3168/jds.2011-4236
|View full text |Cite
|
Sign up to set email alerts
|

Persistency of methane mitigation by dietary nitrate supplementation in dairy cows

Abstract: Feeding nitrate to dairy cows may lower ruminal methane production by competing for reducing equivalents with methanogenesis. Twenty lactating Holstein-Friesian dairy cows (33.2±6.0 kg of milk/d; 104±58 d in milk at the start of the experiment) were fed a total mixed ration (corn silage-based; forage to concentrate ratio 66:34), containing either a dietary urea or a dietary nitrate source [21 g of nitrate/kg of dry matter (DM)] during 4 successive 24-d periods, to assess the methane-mitigating potential of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
149
7
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(208 citation statements)
references
References 23 publications
(36 reference statements)
28
149
7
14
Order By: Relevance
“…No individual MetHb measurement was >15% of total Hb which was substantially <30% total Hb, the value associated with clinical symptoms of methaemoglobinemia (Bruning-Fann and Kaneene, 1993). This agrees with most studies in which animals were adapted slowly to dietary nitrate by increasing nitrate intakes over a period of weeks (cattle:, Hulshof et al, 2012;Van Zijderveld et al, 2011 andsheep: Li et al, 2012;Van Zijderveld et al, 2010). Slow adaptation to dietary nitrate allows the rate of reduction of nitrite to ammonia by the rumen microflora to increase and prevents accumulation of nitrite in the rumen and absorption from the rumen and thereby avoids conversion of haemoglobin to MetHb (Lee and Beauchemin, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…No individual MetHb measurement was >15% of total Hb which was substantially <30% total Hb, the value associated with clinical symptoms of methaemoglobinemia (Bruning-Fann and Kaneene, 1993). This agrees with most studies in which animals were adapted slowly to dietary nitrate by increasing nitrate intakes over a period of weeks (cattle:, Hulshof et al, 2012;Van Zijderveld et al, 2011 andsheep: Li et al, 2012;Van Zijderveld et al, 2010). Slow adaptation to dietary nitrate allows the rate of reduction of nitrite to ammonia by the rumen microflora to increase and prevents accumulation of nitrite in the rumen and absorption from the rumen and thereby avoids conversion of haemoglobin to MetHb (Lee and Beauchemin, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent results in the literature demonstrate, over the short-term, that dietary nitrate can be successfully administered at levels capable of reducing CH 4 with no adverse effects on performance in sheep (Van Zijderveld et al, 2010;Li et al, 2012;El-Zaiat et al, 2014), goats (Nguyen et al, 2010), dairy cows (Van Zijderveld et al, 2011) and beef cattle (Huyen et al, 2010). However, a comprehensive review by Bruning-Fann and Kaneene (1993) reported a reduction in feed intake when nitrate was included in the diet at 10 g nitrate/kg DM (cattle) and 30 g nitrate/kg DM (sheep).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Decreasing dietary protein concentration to address NH 3 and N 2 O losses from stored manure or manure-amended soil may increase enteric CH 4 emissions, as shown by the modelling work of Dijkstra et al (2011b). Low-protein diets for ruminants should be balanced for ruminally degradable protein in order to not impair microbial protein synthesis and fibre degradability in the rumen.…”
Section: Interactions and Links With Productivitymentioning
confidence: 99%
“…Recent research on sheep (Sar et al, 2004;Nolan et al, 2010;van Zijderveld et al, 2010) and cattle (van Zijderveld et al, 2011a and2011b;Hulshof et al, 2012) has shown promising results with nitrates decreasing enteric CH 4 production by up to 50%. Nitrates may be particularly attractive in developing countries where forages contain negligible levels of nitrate and insufficient CP for maintaining animal production.…”
mentioning
confidence: 99%